2002
DOI: 10.1007/s001130100301
|View full text |Cite
|
Sign up to set email alerts
|

Ist niedrig-intensiver Ultraschall bei der Behandlung von Frakturheilungsstörungen wirksam?

Abstract: This prospective consecutive study judges the effectiveness of pulsed low-intensity ultrasound for treatment of boney healing disorders. 86 out of 100 treatments were successful. Although in these 100 cases 64 delayed unions and 36 nonunions were enrolled ultrasound therapy was performed as an alternative to the indicated operation in every case. Excluding ten cases of ununited fractures of the scaphoid no additional therapy was performed in any case. Stratifying the data no significant differences in healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Of interest, patient age, patient gender, smoking habit, fracture age, and number of prior procedures had no impact on outcome. Moreover, it should be appreciated that PWSI !3 months was used as a prerequisite of eligibility, to avoid bias from concurrent use of surgery [4,25,[27][28][29][31][32][33][34]. This provides evidence that LIPUS can LIPUS was used as an adjunct to surgery in several studies reported here [9,26].…”
Section: Results Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Of interest, patient age, patient gender, smoking habit, fracture age, and number of prior procedures had no impact on outcome. Moreover, it should be appreciated that PWSI !3 months was used as a prerequisite of eligibility, to avoid bias from concurrent use of surgery [4,25,[27][28][29][31][32][33][34]. This provides evidence that LIPUS can LIPUS was used as an adjunct to surgery in several studies reported here [9,26].…”
Section: Results Of Analysismentioning
confidence: 99%
“…A total of 4611 references were evaluated ( Fig. 1) to yield 10 eligible references on LIPUS treatment of human fracture nonunions [4,9,[25][26][27][28][29][30][31][32]. Three references [33][34][35] were obtained outside the scope of the PubMed search, while 4608 references were found by PubMed.…”
Section: Search Processmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,15,16,26 Clinical studies also show faster healing rate with ultrasound stimulation. 6,10,11,14,20 In vivo studies show increased mechanical strength in bone tissues after ultrasound application in different stages of bone healing.…”
Section: Introductionmentioning
confidence: 95%
“…Durch die Anwendung von niederenergetischem, gepulstem Ultraschall konnte in klinischen und experimentellen Studien eine Verbesserung der Frakturheilung nachgewiesen werden [2,3,6,11,13,14,15,17]. Dabei konnte eine Verkürzung der Heilungszeit von bis zu 38% im Vergleich zu unbehandelten Patienten belegt werden.…”
Section: Klinische Anwendungen Von Niederenergetischem Gepulstem Ultunclassified